Green managament and its application in the hotel industry - Zapadlo, Kateřina; Jenčková, Jiřina; Zdenková, Karolína; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The thesis deals with the issue of green management and its application into a hotel. Its purpose is to analyse a selected accommodation facility and to propose a new ecological element application based on the results of the analysis. The thesis also describes a situation among Czech and European ecohotels. There is also a chapter about the motivation of clients making a reservation in a ecohotel.
Vedoucí práce: Jiřina Jenčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: cestovní ruch [obor dipl. práce]; diplomové práce; master's theses